Impact of Covid-19 Pandemic on Financial Performance Banking Sector - Annisa Nadiyah Rahmani; Asri Suangga; Lasmanah Lasmanah; Radhitya Pradiftha Drajat; Tasya Permatasari (Universitas Islam Bandung, 2022)
The aim of researcher here is to provide information whether the COVID-19 pandemic had an impact on banking in Indonesia, especially for banks listed on the Indonesia Stock Exchange. The impact on banking is measured by using financial performance ratios, namely Return on Assets (ROA), Net Profit Margin (NPM), Operational Profit Margin (OPM), Loan to Funding Ratio (LFR). Researchers used comparative data on financial statements, namely in 2019 and 2020. The tool used by researchers to process research data was SPSS 24.